Using fuzzy DEMATEL and fuzzy Similarity to develop a human capital evaluation model - Ebrahimi, Elham; Fathi, Mohammad Reza (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
The main purpose of this paper is to propose a suitable model for Human Capital (HC) performance evaluation. In this regard, first a framework for HC components and their relative indicators is constructed through a comprehensive survey of the related literature and confirmatory factor analysis is applied to validate this frame work. Then by considering the possible interrelationships among the HC components, fuzzy Decision Making Trial and Evaluation Laboratory (DEMATEL) method is applied to determine the relative importance of these components. Moreover a novel fuzzy Multiple Criteria Decision Making (MCDM) method, fuzzy Similarity, is respectively introduced for the purpose of ranking organizations in terms of HC components and their indicators. The feasibility of the proposed model is demonstrated by applying the framework of HC and determining the relative weights of HC components through fuzzy DEMATEL method in three Iranian companies which are working in the field of electric power and energy. Finally these three companies are ranked based on their HC capability through fuzzy Similarity method.